2013
DOI: 10.1038/pr.2013.247
|View full text |Cite
|
Sign up to set email alerts
|

Oligohydramnios increases the risk of respiratory hospitalization in childhood: a population-based study

Abstract: Background: Pulmonary hypoplasia is associated with reduced lung function in infancy. The aim of this study was to evaluate the hypothesis that children exposed to oligohydramnios display an increased risk of hospitalization for respiratory illness by using a population-based matched-cohort design. Methods: We used three nationwide population-based data sets to identify 5,228 women who gave birth during 2004 to 2007 and were diagnosed with oligohydramnios during the third trimester of pregnancy. A cohort of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 32 publications
(33 reference statements)
0
8
0
2
Order By: Relevance
“…These conditions are encountered due to a fetal exposure to an oligohydramnios. It causes pulmonary hypoplasia and an 80% higher risk of respiratory failure as compared to unaffected fetuses (Chien et al 2014 ). An oligohydramnios is often part of an autosomal recessive polycystic kidney disease.…”
Section: Pseudoglandular Stage (Weeks 5–17)mentioning
confidence: 99%
“…These conditions are encountered due to a fetal exposure to an oligohydramnios. It causes pulmonary hypoplasia and an 80% higher risk of respiratory failure as compared to unaffected fetuses (Chien et al 2014 ). An oligohydramnios is often part of an autosomal recessive polycystic kidney disease.…”
Section: Pseudoglandular Stage (Weeks 5–17)mentioning
confidence: 99%
“…17,18 However, little has been reported regarding long-term outcomes in children born after pregnancies complicated by IO, especially when assessed as an independent variable. Long-term complications of IO were previously reported by Chien et al 19 , in which an increased risk of respiratory-related hospitalizations was suggested in IO exposed offspring. In addition, an increased risk for cerebral palsy (CP) or even death at 18 months was described by Sasahara et al, 20 though, unlike our study, this study was designed for preterm small for gestational age infants born with oligohydramnios.…”
Section: Introductionmentioning
confidence: 67%
“…48 However, the long-term effects of oligohydramnios on the respiratory system are unknown. In a retrospective cohort study, Chien et al 49 observed that oligohydramnios-exposed children had an 8% higher incidence rate of respiratory hospitalization (ICD-9-CM: 493, 494, 496, 512, 518, 786.00, 786.05, 786.07, 786.09, 786.1e786.4, 799.02, or 799.1, 466, 480e487, 490, 491, 510, or 513, 786) and an 80% higher incidence rate for respiratory failure (ICD-9-CM: 96.70, 96.71, or 96.72) compared with children without oligohydramnios exposure. This risk remained following adjustment for neonatal characteristics, parental demographics, insurance eligibility group, urbanization level of insurance registration area, level of prenatal care, and maternal risk factors.…”
Section: Effect Of Oligohydramnios On Respiratory Outcomes In Childrenmentioning
confidence: 99%
“…However, the underlying mechanism by which oligohydramnios alters the respiratory system and its effects on long-term respiratory outcomes remain unclear. According to a series of studies with an established animal model 29,34,37,42 and a population-based study, 49 a schematic diagram illustrating prenatal exposure to oligohydramnios and the implications for subsequent respiratory disease is provided in Figure 2.…”
Section: Effect Of Oligohydramnios On Respiratory Outcomes In Childrenmentioning
confidence: 99%